An overview of Malaysia Green Technology Corporation Office Building: a showcase energy-efficient building project in Malaysia - Ng, Ban Huat; Akasah, Zainal Abidin (2011)
Malaysia Green Technology Corporation office building is designed based on Zero Energy Building (ZEB) concept; however its Building Energy Index (BEI) has yet to achieve zero. This research focuses on the application of energy-efficient design of the office building; identify the problems causing BEI of the studied office building which did not achieve zero BEI; and to propose approaches that can improve energy efficiency for the office building. Interviews session with the office building management team, architect and energy consultant have been carried out. The outcome of the research shows that energy-efficient design and renewable-energy technology applied in the office building are passive design, active systems, and building integrated photovoltaic systems (BIPV). The inefficiency in the cool part of the cooling system, air movement, and chillers are the problems that have been identified. It is recommended that, continuous research is needed to ensure ZEB concept applied effectively in each type of buildings.